ECN Spray G: Coupled Eulerian internal nozzle flow and Lagrangian spray simulation in flash boiling conditions. (April 2023) - Duronio, Francesco; Di Mascio, Andrea; Villante, Carlo; Anatone, Michele; De Vita, Angelo
Flash-boiling of fuel sprays occurs when a super-heated fuel is discharged into an environment whose pressure is lower than the saturation pressure of the fuel and can dramatically alter spray formation due to complex two-phase flow effects and rapid droplet vaporization. In gasoline direct injection (GDI) engines, typically, it occurs during the injection process when high fuel temperatures make its saturation pressures higher than the in-cylinder one. Flash boiling significantly affects the spray structure and fuel-air mixture formation, with, potentially, if spray collapse is avoided, positive consequences for the engine performance and pollutant emissions. Hence, this paper developed a modelling approach based on the coupling of Eulerian multi-phase and Eulerian-Lagrangian simulations to reproduce flash boiling sprays physics. It allows a comprehensive description of the flash-boiling phenomena that begins within the injector's ducts and continues outside, where a particular mechanism for primary breakup occurs. Experimental data of the Engine Combustion Network (ECN) Spray G injector, covering various operating conditions, were exploited to assess the reliability of the numerical technique adopted. The validation was performed taking into account various parameters such as axial liquid and vapour penetrations, droplet size and images regarding the near-nozzle zone. The numerical model achieves a pretty good level of agreement with the experimental data and, in particular, it is sensitive to the spray behaviour in the different operating conditions.